+0  
 
+1
133
3
avatar

i*i= -1 right?

Guest Jul 25, 2017
Sort: 

3+0 Answers

 #1
avatar
0

Sqrt(-1) = i

i^2 =sqrt(-1) x sqrt(-1) = - 1 (you got it right)

i^3 = -1 x i = -i

i^4 =-1 x -1 = 1 Then the pattern repeats.

Guest Jul 25, 2017
 #2
avatar+6896 
0

Yup correct.

MaxWong  Jul 25, 2017
 #3
avatar+20 
+2

\(\sqrt{-1}=i\)

\(i \times i = \sqrt{-1} \times \sqrt{-1} = {\sqrt{-1}}^{2} = -1\)

yes.

PkmnQ  Jul 26, 2017

28 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details